APLIKASI GOOD GOVERNACE PEMERINTAH KECAMATAN DI KECAMATAN RASAU JAYA KABUPATEN KUBU RAYA - Sujendra, Bima (JURNAL BORNEO AKCAYA, 2017)
Applications Good Governace District Government Rasau In District Kubu Raya Jaya selected researchers are encouraged by the phenomenon is still not maximal implementation of good governance in Sub Rasau Jaya, it's still not expected because of the implementation of the principles of good governance right. To that end, the general problem of research formulated: "How Good Governace District Government Applications In District Rasau Jaya Kubu Raya". The study design used a qualitative approach. The results showed that in general the public services that promote the principles of Good Governance in Sub Rasau Kubu Raya have been implemented, although not yet fully maximized. The principle of participation as one of the principles of good governance is still visible not optimal, it's like what was said by the employees of the district office "people are less active in following the activities carried out by the district government, they tend to be busy farming". In the principle of the Rule of Law (Rule of Law) is still discrimination between Kecamtan government officials with an acquaintance. Principle responsive (responsiveness) in the implementation of public services, it is seen still lambanya work done by the sub-district employees in service delivery.